Role of G-proteins in islet function in health and diabetes - Kowluru, Anjaneyulu (Diabetes Obes Metab, 2017)
Glucose-stimulated insulin secretion [GSIS] involves interplay between metabolic and cationic events. Seminal contributions from multiple laboratories affirm essential roles for small G-proteins [Rac1, Cdc42, Arf6, Rab27A] in GSIS. Activation of these signaling proteins promotes cytoskeletal remodeling, transport and docking of insulin granules on the plasma membrane for exocytotic secretion of insulin. Evidence in rodent and human islets suggests key roles for lipidation [farnesylation and geranylgeranylation] of these G-proteins for their targeting to appropriate cellular compartments for optimal regulation of effectors leading to GSIS. Interestingly, however, inhibition of prenylation appears to cause mislocalization of non-prenylated, but [paradoxically] activated G-proteins, in “inappropriate” compartments leading to activation of stress kinases and onset of mitochondrial defects, loss in GSIS and apoptosis of the islet β-cell. This review highlights our current understanding of roles of G-proteins and their posttranslational lipidation [prenylation] signaling networks in islet function in normal health, metabolic stress [glucolipotoxicity and ER stress] and diabetes. Critical knowledge gaps that need to be addressed for the development of therapeutics to halt defects in these signaling steps in β cells in models of impaired insulin secretion and diabetes are also highlighted and discussed.